Ijma’ Sukuti dalam Pelebaran Mas’a dan Mina Jadid Perspektif Sumber-Sumber Utama Hukum dalam Ushul Fiqh - Mohamad Toha Umar (Jurnal Syariah dan Hukum Komparatif, 2022)
By definition, ijma’ sukuti means a condition when one or more mujtahids express an opinion on a problem that is widespread in the community and the other mujtahids do not respond or remain silent with that opinion. Opinions in this case can be in the form of fatwas or legal decisions. The most well-known practice of ijma’ sukuti is the legal decision imposed by Amirul Mu’minin Umar bin Khattab which punishes alcohol drinkers with 80 lashes. Originally, in the hadith it is stated that the punishment for drinking khamr is 40 lashes. Umar added that the sentence was doubled on the grounds that 40 lashes were used as punishment for drinking khamr and 40 lashes as a punishment for drinking khamr must have done something disturbing to the public because he was drunk. As for the connection with the widening of masya’irul haram places, such as in the area of pilgrimage rituals, including those carried out by Khadimul Haramain al-Sharifain at the agreement of Saudi scholars and silenced by world scholars, it is a manifestation of the methodology of ijtihad of fiqh law with the ijmak sukuti model. This article uses the ushul fiqh approach by exploring the sources of Islamic law